1994
DOI: 10.1002/mrd.1080380405
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic development of bovine oocytes matured in vitro for 24 hr and activated by ethanol and cycloheximide

Abstract: This research was undertaken to improve development of parthenogenetic embryos following various combined treatments of ethanol and cycloheximide. In Experiment 1 in vitro matured oocytes (IVM, 24 hr) were treated with 7% ethanol for 5 min followed by incubation in 10 micrograms/ml cycloheximide in Medium 199 for 0 (control), 5, 10, and 20 hr. Development to 2-8 cells following culture for 3 days was similar among treated groups (32-41%; P > 0.05), which was higher than that of controls (6%; P < 0.05). Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
50
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 39 publications
7
50
0
Order By: Relevance
“…CCB and CCD have been widely used to prevent extrusion of pseudo PBs of G0/G1 somatic donors during the SCNT procedure [3]. With a similar purpose, exposure to these chemicals at different times, such as 1, 5 or 6 hr, have also been attempted in bovine [1,11,20,24,38]. In the present study, groups 1-4 showed extrusion rates ranging from 53-67%, whereas group 5 exhibited a significantly low rate of 22%.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…CCB and CCD have been widely used to prevent extrusion of pseudo PBs of G0/G1 somatic donors during the SCNT procedure [3]. With a similar purpose, exposure to these chemicals at different times, such as 1, 5 or 6 hr, have also been attempted in bovine [1,11,20,24,38]. In the present study, groups 1-4 showed extrusion rates ranging from 53-67%, whereas group 5 exhibited a significantly low rate of 22%.…”
Section: Discussionmentioning
confidence: 70%
“…Liu et al [19] reported 27% blastocyst rates using CHX combined with 2.5 µg/ml CCD for 6 hr after Ca 2+ ionophore treatment, but they could not obtain development to the hatched blastocyst stage. Presicce and Yang [24] also reported that the combination of CHX with CCB after ethanol treatment could improve the development of bovine parthenotes. Improved development after treatment with CCB or CCD may be due to their ability to induce diploid parthenotes by preventing cytokinesis, and formation of diploid embryos is similar to that of the normal fertilization process, thus, resulting in better developmental rates [19,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation is an important step in the NT procedure and ethanol and ionomycin have been widely used as activating agents in several species, such as cattle [15,20,21], mice [8], sheep [16], and goats [1,4,6,11,32]. There are a few reports on the development of goat oocytes after parthenogenetic activation by treatment with ionomycin and ethanol, both followed by exposure to 6-diethylaminopurine (6-DMAP) [17,18].…”
mentioning
confidence: 99%